The Environmental Impact of Landfill Expansion in Ijobalit Village, East Lombok Regency - Adyatama, Bayu; Utami, Annisa Seminar; Matindas, Krishnarini (Jurnal Biologi Tropis, 2025)
Waste management issues in Indonesia are a major concern due to the high volume and poor management systems in many Final Processing Sites (TPAs). This study aims to analyze the impact of the expansion of the Ijobalit Landfill in East Lombok Regency on the environment and social dynamics of the surrounding community. The research uses a qualitative approach with an embedded single case study design. Data was collected through field observation and in-depth interviews, then analyzed using NVivo 12 Plus software. The results showed that the expansion of the landfill was carried out without meeting the operational standards (SOP) and SNI, causing various negative impacts, such as water and air pollution, declining the quality of agricultural land, health problems, and social unrest in the community. Economically, landfills do not make a significant contribution to the welfare of the community. The conclusions of this study emphasize the importance of sustainable and participatory landfill management. This study recommends the need for ecological and social-based waste management policies, involving communities in every stage of planning and decision-making.